Cardiac tamponade secondary to iatrogenic needle decompression in blunt force trauma. Issue 4 (9th June 2022) - Faizi, Zaheer; Morales, Joseph; Hlopak, Joseph; Batool, Amber; Ratnasekera, Asanthi
Abstract: The proper treatment for tension pneumothorax is rapid needle decompression. This procedure is frequently performed in the field for trauma patients who have clinical symptoms of pneumothorax. The procedure itself has a high rate of failure due to improper placement, operator inexperience, or chest wall thickness. A 22-year-old unrestrained driver in a high-speed motor vehicle collision was found unconscious and subsequently had needle decompression for decreased breath sounds in the field. The patient was initially stable upon arrival but progressed to cardiac arrest. She had a thoracotomy in the emergency department that showed cardiac tamponade followed by return of spontaneous circulation. On formal thoracotomy, it was discovered that the patient had an iatrogenic cardiac injury from the angiocatheter placed during needle decompression. Needle decompression is a lifesaving procedure, but it is associated with high failure rates and possibility for iatrogenic injury.